2013
DOI: 10.7884/teke.223
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite Öğrencilerinin Okuma Stratejileri Üstbilişsel Farkındalık Düzeyleri (

Abstract: Bu araştırmada İnönü Üniversitesi'nde öğrenim gören öğrencilerin okuma stratejileri üstbilişsel farkındalık düzeyleri belirlenmiştir. Bu amaç doğrultusunda, "Öğrencilerin okuma stratejileri üstbilişsel farkındalık durumu ne düzeydedir? Öğrencilerin okuma stratejileri üstbilişsel farkındalık durumu okudukları fakültelere göre anlamlı değişiklik gösteriyor mu? Öğrencilerin okuma stratejileri üstbilişsel farkındalık durumu cinsiyete göre istatistiksel olarak anlamlı değişiklik gösteriyor mu?" sorularına cevap ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
6
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
5
6
0
4
Order By: Relevance
“…The finding regarding the higher scores by female participants in planning reading is consistent with the study by Karatay (2009). On the other hand, the finding that female participants had higher levels of cognitive awareness of reading strategies is consistent with the findings reported in the studies by Ateş (2013) and Koç and Arslan (2017). In this study, it was found that pre-service Turkish language teachers had higher scores in planning, organization and evaluation of books.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…The finding regarding the higher scores by female participants in planning reading is consistent with the study by Karatay (2009). On the other hand, the finding that female participants had higher levels of cognitive awareness of reading strategies is consistent with the findings reported in the studies by Ateş (2013) and Koç and Arslan (2017). In this study, it was found that pre-service Turkish language teachers had higher scores in planning, organization and evaluation of books.…”
supporting
confidence: 91%
“…As there are limited number of studies on training of pre-service teachers in reading strategies (Klapwijk, 2012), it is hoped that this study will make a contribution in determining the variables that are effective in planning the education to be given to pre-service teachers to improve their students' reading strategies. Existing studies mostly deal with metacognitive awareness of preservice teachers on reading strategies (Dilci & Babacan, 2011;Karadüz, 2011;Mert, 2015;Özdemir, 2018;Topuzkanamış & Maltepe, 2010) and the effects of some variables such as gender, major, year of study and number of books read (Ateş, 2013(Ateş, , Çeliköz, 2018Çöğmen, 2008;Erdem, 2012;Karatay, 2009;Karasakaloğlu, Saracaloğlu & Yılmaz-Özelçi, 2012;Koç & Arslan, 2017;Kurnaz & Akaydın, 2015;Kuş & Türkyılmaz, 2010;Özdemir, 2018;Özden, 2018;Topuzkanamış & Maltepe, 2010). The current study not only deals with the effects of gender, year of study, major and frequency of reading books on pre-service teachers' reading strategies, but it also analyzes the effects of other variables such as preferences in reading materials, types of books read and materials researched.…”
Section: Extended Abstract Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu bölümde araştırmanın birinci alt problemine yönelik bulgular yer almaktadır. (Akçam, 2012;Aktaş, 2013;Alcı & Altun, 2007;Ateş, 2013;Bağçeci, Döş & Sarıca, 2011;Canca, 2005;Demir & Özmen, 2011;Dilci & Kaya, 2012;Saban & Saban, 2008;Topçu & Tüzün, 2009;Tunca & Şahin, 2014). Üstbilişsel farkındalığın cinsiyet değişkenine göre anlamlı düzeyde farklılık göstermediği çalışmalar da bulunmaktadır (Aydın & Coşkun, 2011;Balcı, 2007;Çikrıkci & Odacı, 2013;Kışkır, 2011;Memnun & Akkaya, 2009;Özsoy & Günindi, 2011;Sapancı, 2012;Tüysüz, Karakuyu & Bilgin, 2008 (Baltacı, 2009;Demircioğlu, 2008;Demirsöz, 2010;Ektem, 2007;Gelen, 2003).…”
Section: üStbilişsel Farkındalık Düzeyinin Farklılığıunclassified
“…In addition, it was determined in this study that the participants used moderate level of metacognitive reading strategies and the problem solving strategies were the most frequently used strategy. Similarly, Ateş [5] determined that the students used metacognitive strategies in moderate level during reading and their problem solving skills were high. These results showed that metacognitive reading strategies were important in problem solving skills.…”
Section: Conclusion and Discussionmentioning
confidence: 99%